Video-Based Education Improves Fainting First Aid Knowledge in Indonesian Red Cross Youth - T. Abdur Rasyid; Bayu Saputra; Sandra Sandra; Rani Lisa Indra; Defi Eka Kartika; Aurora Dhiva Putri (Karya Kesehatan Siwalima, 2026)
Sudden loss of consciousness from reduced cerebral blood flow remains common in schools, especially during flag-raising ceremonies and strenuous activity, and improper management increases injury risk. Indonesian Red Cross Youth (PMR) members serve as key first responders in schools, yet their knowledge of fainting management is often limited. This activity aimed to improve PMR members' knowledge of first aid for fainting through video-based education at SMA Negeri 10 Pekanbaru. Conducted on 29 August 2025 with 50 students, it used a 5-minute-50-second educational video followed by discussion. Knowledge was assessed pre- and post-intervention using a validated 15-item questionnaire (CVI 0.625–0.875) on fainting definitions, causes, symptoms, and first aid steps. Mean scores increased significantly from 52.9 (SD 15.0) to 74.0 (SD 19.9), a 39.8% rise, while good knowledge among participants grew from 2% to 62% (t = 6.79; p < 0.001). The program effectively improved PMR members' preparedness and is recommended for replication among adolescent peer groups.